The influence of structural and functional changes on N-P-K input of agricultural origin and surface water quality in the upper Dunajec River basin in the years 1980–2010 - Kopacz, Marek; Kowalczyk, Agnieszka; Smoroń, Sylwester; Rychtarczyk, Marta (Geology, Geophysics and Environment, 2018)
The aim of the study was the prediction of N-P-K inputs (hereafter referred to as NPK load) from agricultural sources. The study aimed to determine relations between the structural changes and the N-P-K load (nitrogen-phosphorus-potassium) fertilizer components in the upper Dunajec River basin (the Carpathian region in Poland). Analysis included the level and nature of agricultural production, the land use structure and non-agricultural factors. Multiple regression analysis was used for the development of the model. Relationships were determined in the form of regression models in the system of N-P-K load-structural parameters-land use-surface water quality. The quality of surface water was assessed in a range of concentrations of N-NO3-, N-NH4+, PO43-, Cl-, and compared to the N-P-K load that was brought to the basin from agricultural sources. Significant structural and spatial changes took place in the upper Dunajec River basin that affected many social, economic and environmental factors. Agricultural production was reduced, resulting in a decrease of area of agricultural land between the year 1980 and 2010. The most important factors influencing the changes in biogenic load of an agricultural origin were: stocking density and mineral fertilization. Both of these parameters determined the amount of N-P-K load in approx. 80-90% (not counting the use of N-P-K components by crops). Surface water quality has generally improved, only higher concentrations of chlorides were recorded in small urbanized river basins. Therefore, the chemical composition of water plays the role of a simplified indicator of structural changes. Mathematical formulas proved changes in N-P-K load depending on variations of individual influencing factors. The development of the usable space of the investigated river basin must take into account agricultural and non-agricultural factors, as well as the proportions and relationships between them. Only then might the sustainable and multifunctional development of these areas be provided.